Discovery of small molecule inhibitors of chikungunya virus proteins (nsP2 and E1) using in silico approaches. Issue 4 (4th March 2021) - Khan, Naushad; Bhat, Ruchika; Patel, Ashok K.; Ray, Pratima
Abstract: Chikungunya virus (CHIKV) has emerged as a major viral threat, affecting over a million people worldwide per year. It is a vector borne disease transmitted to the human by Ades mosquitoes and primarily affect people by causing viral fever, severe joint pain and other symptoms, like rash, joint swelling, muscle pain and in rare cases can be fatal. CHIKV is a deadly virus, with its mutation rate found to be significantly higher as compared to other viruses. To date, there has been no reported FDA approved drug against this virus. Thus, keeping in mind the urgent need to scrutinize potential therapies against CHIKV, the present study identified twenty plant bioactive compounds that are available at low price and do not have associated adverse effect. For identification of active potentials molecules the pharmacoinformatics-based perspective was applied against CHIKV structural (E1) and non-structural (nsP2) proteins using molecular docking and scoring. The selected compounds were further studied for pharmacokinetics (PK) and pharmacodynamics (PD) associated parameters such as initial absorption, then distribution and later on metabolism excretion and toxicity (ADMET) profiles based on in silico study. The results reveal five potential lead compounds having high binding energy that can help in the development of commercial drugs with favorable ADMET characteristic. Communicated by Ramaswamy H. Sarma